Institutions and small settler economies : a comparative study of New Zealand and Uruguay, 1870-2008 - Schlueter, Andre; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2014)
Institutions and Small Settler Economies provides a comprehensive improvement in our understanding of institutional contributions to economic growth.
Keywords: States, Small -- Economic conditions -- Case studies; New Zealand -- Economic conditions; New Zealand -- Social conditions; Uruguay -- Economic conditions; Uruguay -- Social conditions